Optimasi Sterilisasi Eksplan Daun Tanaman Lidah Mertua (Sansevieria sp.) pada Kultur In Vitro - Ade Tiyan Handayani; Edhi Sandra; Hanik Faizah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
The existence of Sansevieria sp. as an ornamental plant that has many benefits preserved. However, conventional propagation requires a lot of materials and time long. Leaf cuttings are only able to produce 1-2 plants in 2 months, and stop when they are aged 5 months. While the separation of tillers (Tillering) only produces 2-3 plants from 1 clump for 5 months. Tissue culture can be the solution, but sterilization must be done to minimize contamination without killing explants. The research aims to find out optimal concentration of HgCl2 and duration of shaking on the sterilization of Sansevieria leaf explants sp.. The research design used a completely randomized design with 2 factors. first factor namely the concentration of HgCl2 with 3 levels (4%, 7%, and 10%,) and the second factor is duration shuffled with 4 levels (3, 5, 7, and 9 minutes). Each treatment includes a negative control performed at the time of explant sterilization in Laminar Air Flow. Data analyzed by test ANOVA or Kruskal-Wallis. Followed by the 5% BNJ test if it is significantly different. Results show that the concentration of HgCl2 has a significant effect on the parameters of the initial time of contamination, the mass sterility of explants, and percentage of browning explants, but had no significant effect on percentage of contaminated explants. Concentration that is too high can slow down the appearance of contamination, prolonging the sterile period, but causing browning of explants. Known that the duration of explant shaking in HgCl2 had no significant effect on all parameter. The use of 10% HgCl2 with a shaking duration of 7 minutes (H3P3) is known to be the most effective optimal for sterilization of explants Sansevieria sp. because it is able to reduce external contamination, prolongs the sterile period up to 12.33 HST, and does not cause too many explants browning that is 33.33%.